(untitled) (Stavební obzor - Civil Engineering Journal, 2019)
The surface deformation caused by underground coal mining will cause great damage to the surface buildings. Especially for the strip foundation buildings, the surface horizontal deformation will cause the walls to crack and open, threatening the safe use of buildings. However, there is lacking research on the failure mechanism of strip foundation buildings caused by surface horizontal deformation. Therefore, it is particularly important to study the mechanism. In this paper, a mechanical model of additional stress distribution in the strip foundation under surface horizontal deformation is established. Based on the model, the internal stress variation characteristics of the longitudinal wall of strip foundation buildings are studied with different factors: friction coefficient, surface curvature, foundation load and foundation length under the surface horizontal deformation. The internal stress variation of the transverse wall of the strip foundation buildings is analysed. The theory is verified by numerical simulation and a case study from Fengfeng coalmine China. Finally, the protection methods of the strip foundation buildings under the surface horizontal deformation are proposed.